Impairment of microcirculation in juvenile idiopathic arthritis - studies by nailfold videocapillaroscopy and correlation with serum levels of sICAM and VEGF. - Slawomir Chlabicz; Miroslawa Urban; Otylia Kowal-Bielecka; Anna Gorska; Jerzy Sienkiewicz; Stanislaw Gorski (Folia Histochemica et Cytobiologica, 2009)
Impairment of vascular endothelium plays a key role in the pathogenesis of inflammatory diseases including juvenile idiopathic arthritis (JIA) and atherosclerosis. We hypothesized that structural abnormalities of the smallest blood vessels (capillaries) might exist and reflect endothelial dysfunction in children with JIA. Microcirculation was studied, by means of nailfold videocapillaroscopy with computer-associated image analysis, in 43 patients with JIA and compared with 20 healthy children. Moreover, capillaroscopic findings were correlated with the activity of the disease and the levels of serum biomarkers of endothelial injury, namely soluble intercellular adhesion molecule (sICAM) and vascular endothelial growth factor (VEGF). We found that in JIA patients capillaries were significantly wider and longer than in healthy controls. Moreover, irregular capillaries and dilated subpapillary venous plexus were found significantly more frequently in JIA in comparison with the control group. Serum levels of sICAM and VEGF were significantly higher in JIA patients with capillary abnormalities than in JIA patients with normal capillaroscopy. Our study indicates that there are structural changes in the microcirculation of patients with JIA and that these changes might reflect endothelial injury. Whether capillaroscopy might have a role in early identification of JIA patients being at higher risk of atherosclerosis requires further studies.